Management of severe ovarian hyperstimulation syndrome with thawed plasma - Mohan S Kamath; Asmita Joshi; Anne Marie Kamath; T K Aleyamma (Wolters Kluwer Medknow Publications, 2013)
Severe ovarian hyperstimulation syndrome remains one of the life threatening complication of assisted reproductive technology. In refractory cases of late ovarian hyperstimulation syndrome (OHSS), clinicians are left with limited therapeutic options. We report a case of refractory OHSS which was managed successfully using thawed plasma. Thawed plasma transfusion could be potential therapeutic option for managing patients with severe ovarian hyperstimulation not responding to conventional treatment.